Penyelundupan dan Terbentuknya Kawasan Ekonomi Maritim Wakatobi Tahun 1980-an - La Ode Rabani (Universitas Gadjah Mada, 2016)
This paper explains three important factors that affected the history of Wakatobi economic area shifting in Southeast Sulawesi.First, global market commodities such as duralex, bicycles, motorbikes, mechanized boats were easier to find and came earlier in this area than other regions.Second, illegal trading (smuggling) was likely to happen because of the lax of authorities in guarding its sea areas between 1950’s-1990’s.Third, the capital accumulation in this area pushed the improvement of the economic infrastuctures that lead to market expansion to Eastern Indonesia.